Sulphanilamide in the treatment of pulmonary tuberculosis with special reference to its action on the blood sedimentation rate - Salzmann, Kenneth Douglas (The University of Edinburgh, 1940)
(1) The present investigation was stimulated by the absence of any publication concerning the use of sulphanilamide in pulmonary tuberculosis. (2) The pathology of tuberculosis is reviewed briefly including a description of the tubercle bacillus and the process taking place in the lung after infection by the bacillus. (3) The avascular nature of the tubercle is a bar to successful chemotherapy, and for the same reason fibroid lesions are resistant. (4) Adequate contact between the focus and remedial agent can only be achieved by means of hyperaemic lung tissue: such conditions are fulfilled .best by rapidly spreading exudative lesions with or without cavitation (5) When there is rapid tissue destruction there is almost certainly mixed infection and this contributes to systemic disturbance. (6) Acute forms of Tuberculosis, particularly if bilateral, are the most lethal and least responsive to treatment. (7) The composition of sulphanilamide and allied drugs, their favourable action on various micro-organisms, including, an incomplete bacteriostatic action on the tubercle bacillus are described: their toxic effects, influence n the blood and mode of action are discussed. (8) Present, day treatment of tuberculosis is reviewed. The results obtained are recorded and mention is made of the possibility of combining each method with sulpanilamide. Collapse Therapy is relatively ineffective in bilateral disease, gold of doubtful use and often too toxic, and tuberculin is both useless and dangerous if there is much systemic upset. (9) The eighteen cases to whom rubiazol was given are described, and the effect of the drug is estimated by reference to its action on the temperature, pulse, weight, sputum, sedimentation rate etc. (10) Toxic effects were minimal - transient cyanosis and a scarlatiniform rash - both disappearing without stoping treatment. Rubiazol is probably the safest form of sulphanilamide for use over a prolonged period, but frequent examinations of the blood are essential to avoid possible agranulocytosis. (11) Certain blood changes occurred and it is suggested that these may have resulted indirectly from action of rubiazol on the tubercle bacillus itself. (12) The sedimentation rate is not a very precise measure of, improvement. Profound alterations in the rate follow the use of gold and rubiazol together. (13) It is suggested that trial of gold and sulphanliamide should be made in treatment of rheumatoid arthritis. (14) The action of sulphanilamide in tuberculosis is mainly on the secondary infecting organisms - especially the streptococci. (15) Presence in the sputum of streptococci or other organisms than the tubercle bacillus is not, per se, an indication for use of sulphanilamide. There must be evidence of their activity.. (16) Indications for sulphanilamide are rapidly spreading exudative tuberculosis, with or without cavities, a pulse-rate in excess of 95, temperature 100°F or more, copious sputum containing streptococci etc., numerous moist ráles and a rapid sedimentation rate. (17) Speedy improvement in recent tuberculous pleural effusion suggests a possible use for sulphanilamide in this condition, and other early lesions which evoke pyrexia and tachycardia. (18) Sulphanilamide is useless in chronic and indolent forms of tuberculosis unassociated with systemic disturbance. - - - - - Eighteen cases of pleuro-pulmonary tuberculosis were treated with rubiazol a compound closely similar to sulphanilamide. Some of the cases seemed to derive benefit. It is suggested that sulphanilamide is of most use in active lesions with mixed infection. The drug may be of special service in patients for whom collapse therapy, gold and other forms of treatment cannot be used.